Kepastian Versus Keadilan: Benturan Nilai dalam Penerapan Asas Kebendaan Pada Hukum Waris dalam Putusan Mahkamah Agung Nomor 2079 K/PDT/2024 - Saputro, Adi; Suriana, Ricky Kurniawan; Sibarani, Frisko B.; Oktavian, Adi; Noviana, Juwita (Indo-MathEdu Intellectuals Journal, 2025)
This article examines the conflict of values between legal certainty and substantive justice in the application of property law principles in the context of inheritance, with an analysis of the Supreme Court Decision Number 2079 K/Pdt/2024. This research uses a case study method with a juridical-normative approach. The main object of the research is the inheritance dispute case that has received a final and binding decision (inkracht van gewijsde), namely the Supreme Court Decision Number 2079 K/Pdt/2024 concerning a land inheritance dispute in Takalar Regency, South Sulawesi. Data collection was conducted through document studies of court decisions, relevant legislation, and scientific literature in the field of property law and inheritance. The collected data was then analyzed using qualitative analysis methods with a legal hermeneutics approach. The research findings indicate a gap between the formal proof system in positive law and traditional land ownership practices, which results in the rejection of inheritance claims without formal evidence, even when supported by a history of ancestral possession. A humanistic approach to resolving inheritance disputes requires a reorientation of legal goals through the harmonization of the proof system that considers the local context and strengthens alternative dispute resolution mechanisms. The article concludes the importance of land law reform that accommodates legal pluralism while still providing legal certainty.